Deep Brain Stimulation for Pediatric Dystonia: A Review of the Literature and Suggested Programming Algorithm. (October 2022) - Gelineau-Morel, Rose; Kruer, Michael C.; Garris, Jordan F.; Abu Libdeh, Amal; Barbosa, Daniel A. N.; Coffman, Keith A.; Moon, David; Barton, Christopher; Zea Vera, Alonso; Bruce, Adrienne B.; Larsh, Travis; Wu, Steve W.; et al.
Deep brain stimulation (DBS) is an established intervention for use in pediatric movement disorders, especially dystonia. Although multiple publications have provided guidelines for deep brain stimulation patient selection and programming in adults, there are no evidence-based or consensus statements published for pediatrics. The result is lack of standardized care and underutilization of this effective treatment. To this end, we assembled a focus group of 13 pediatric movement disorder specialists and 1 neurosurgeon experienced in pediatric deep brain stimulation to review recent literature and current practices and propose a standardized approach to candidate selection, implantation target site selection, and programming algorithms. For pediatric dystonia, we provide algorithms for (1) programming for initial session and follow-up sessions, and (2) troubleshooting side effects encountered during programming. We discuss common side effects, how they present, and recommendations for management. This topical review serves as a resource for movement disorders specialists interested in using deep brain stimulation for pediatric dystonia.